2022
DOI: 10.1186/s13063-022-06348-z
|View full text |Cite
|
Sign up to set email alerts
|

Getting it wrong most of the time? Comparing trialists’ choice of primary outcome with what patients and health professionals want

Abstract: Background Randomised trials support improved decision-making through the data they collect. One important piece of data is the primary outcome — so called because it is what the investigators decide is the most important. Secondary outcomes provide additional information to support decision-making. We were interested in knowing how important patients and healthcare professionals consider the outcomes (especially the primary outcome) measured in a selection of published trials. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Our original study found that patients and healthcare professionals disagreed with the trial team’s choice of primary outcome 72% of the time [ 1 ]. It does not matter how robust the methodology of a trial is or how experienced the research team is, if the outcome that is most important to people living with a disease (and those treating it) is not measured, or not measured to a sufficient degree of certainty, then it is quite possible that the results will be considered irrelevant.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our original study found that patients and healthcare professionals disagreed with the trial team’s choice of primary outcome 72% of the time [ 1 ]. It does not matter how robust the methodology of a trial is or how experienced the research team is, if the outcome that is most important to people living with a disease (and those treating it) is not measured, or not measured to a sufficient degree of certainty, then it is quite possible that the results will be considered irrelevant.…”
Section: Discussionmentioning
confidence: 99%
“…The methods used to randomly select the original 44 trials have been described previously [ 1 ]. For the current study, the protocol for each of the 44 trials was sought.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations